Kinetics and modelling of kojic acid production by Aspergillus flavus link in batch fermentation and resuspended mycelial system - Ariff, A.B.; Rosfarizan, M.; Herng, L.S.; S., Madihah; Karim, M.I.A. (Rapid Science, 1997)
An unstructured model based on logistic and Luedeking-Piret equations was proposed to describe growth, substrate consumption and kojic acid production by Aspergillus fiavus Link strain 44-1 in batch fermentation and also in a resuspended cell system. The model showed that kojic acid production was non-growth associated. The maximum kojic acid and cell concentrations obtained in batch fermentations using the fermenter with optimized dissolved oxygen control (32.5 g/l and 11.8 g/l, respectively) and using a shake-flask (36.5 and 12.3 g/l, respectively) were not significantly different. However, the maximum specific growth rate and a non-growth-associated rate constant for kojic acid formation (n) for batch fermentation using the fermenter (0.085/h and 0.0125 g kojic acid/g cell.h, respectively) were approximately three and two times higher than the values obtained for fermentation using a shake-flask, respectively. Efficient conversion of glucose to kojic acid was achieved in a resuspended pellet or mycelial system, in a solution containing only glucose with citrate buffer at pH 3.5 and at a temperature of 30 °C. The resuspended cell material in the glucose solution was still active in synthesizing kojic acid after prolonged incubation (up to about 600 h). The rate constant of kojic acid production (n) in a resuspended cell system using 100 g glucose/l was almost constant at an average value of 0.011 g kojic acid/g cell.h up to a cell concentration of 19.2 g/l, above which it decreased. A drastic reduction of n was observed at a cell concentration of 26.1 g/l. However, the yield based on glucose consumed (0.45 g/g) was similar for all cell concentrations investigated.